2017
DOI: 10.1017/s1368980017000362
|View full text |Cite
|
Sign up to set email alerts
|

Energy drinks available in Ireland: a description of caffeine and sugar content

Abstract: Energy drinks are freely available on the island of Ireland and all products surveyed can be defined as highly caffeinated products. This has potential health issues particularly for children and adolescents where safe limits of caffeine have not been determined. Energy drinks surveyed also contained high levels of sugar and could potentially contribute to weight gain and adverse dental health effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 10 publications
0
11
0
Order By: Relevance
“…Energy drinks (EDs) can be defined as nonalcoholic beverages that contain caffeine as the main ingredient and a combination of other components, including guarana extract, taurine, and ginseng. 1,2 According to the recommendations of Health Canada, the maximum caffeine intake levels for children aged 4 to 12 years should be between 45 and 85 mg/day and for children aged 13 years and above should not exceed 2.5 mg/ kg/day. 3 Many reports have described the adverse health effects of ED consumption, including tachycardia, hypertension, confusion, seizures, and agitation.…”
Section: Introductionmentioning
confidence: 99%
“…Energy drinks (EDs) can be defined as nonalcoholic beverages that contain caffeine as the main ingredient and a combination of other components, including guarana extract, taurine, and ginseng. 1,2 According to the recommendations of Health Canada, the maximum caffeine intake levels for children aged 4 to 12 years should be between 45 and 85 mg/day and for children aged 13 years and above should not exceed 2.5 mg/ kg/day. 3 Many reports have described the adverse health effects of ED consumption, including tachycardia, hypertension, confusion, seizures, and agitation.…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, the sugar contents of the same NCSSBs were different across different countries [22]. Although high sugar contents of these products have been found in developed countries [7, 8, 23, 24], no study has reported the sugar and energy content in NCSSBs in China. Considering China has the world’s second largest market of SSBs with the rapidly expanding market of NCSSBs [2], with the growing interest in a policy intervention to reduce the consumption of SSBs at a population level, research to understand the sugar content and energy content in NCSSBs sold in China are urgently needed.…”
Section: Introductionmentioning
confidence: 99%
“…Energy drinks are soft drinks with a high caffeine content, with some drinks containing as much as 505 mg of caffeine per serving and other substances including high dose of sugar, some vitamins, including riboflavin, pyridoxine, nicotinamide, other B vitamins, and various herbal derivatives, which could act as stimulants [ 1 , 2 ]. Energy drinks have been increasingly consumed, especially among adolescents, to sustain alertness and boost energy [ 3 ].…”
Section: Introductionmentioning
confidence: 99%